The Effect of Inflation on Growth - Evidence from a Panel of Transition Countries - Max Gillman; Mark N. Harris (Hungarian Academy of Sciences, Institute of Economics, 2009)
The paper examines the effect of inflation on growth in transition countries. It presents panel data evidence for 13 transition countries over the 1990-2003 period; it uses a fixed effects panel approach to account for possible bias from correlations among the unobserved effects and the observed country heterogeniety. The results find a strong, robust, negative effect on growth of inflation or its standard deviation, and one that appears to decline in magnitude as the inflation rate increases, as seen for OECD countries. And the results include a role for a normalized money demand in affecting growth, as well as for a convergence variable, a trade variable and a government share variable. And robustness of the baseline single equation model is examined by expanding this into a three equation simultaneous system of output growth, inflation and money demand that allows for possible simultaneity bias in the baseline model.
Keywords: C23; E44; O16; O42; 330; growth; transition; panel data; inflation; money demand; endogeneity; Geldpolitik; Inflation; Wirtschaftswachstum; Panel; Transformationsstaaten